Comprehensive Design and Experimental Validation of Tethered Fixed-Wing Unmanned Aerial Vehicles - Changjin Yan; Jinchuan Yang; Donghui Zhang; Shu Zhang; Taihua Zhang (Aerospace)
The limited battery capacity currently restricts the flight duration of unmanned aerial vehicles (UAVs). Additionally, tethered rotorcraft UAVs suffer from low efficiency, and deploying tethered balloons presents significant challenges. Consequently, tethered fixed-wing UAVs exhibit highly promising development prospects. This study designs and constructs both simulation and physical models of a tethered fixed-wing UAV system. With the utilization of methods such as system identification and trust region algorithms, a comprehensive simulation model was developed, and its accuracy was rigorously validated. Furthermore, the feasibility of the system was confirmed through the integration of UAV hardware with a constructed power supply system, incorporating open source flight control software. The results demonstrate that the tethered fixed-wing UAV system is both feasible and reliable, offering rapid deployment capabilities and commendable flight stability. These findings highlight the potential of tethered fixed-wing UAVs as efficient and stable platforms for various applications, laying the groundwork for future research focused on developing more robust and adaptive control systems tailored to the specific challenges posed by tethered operations.